2000
DOI: 10.1016/s0168-6496(99)00105-1
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of 1,1-dichloro-2,2-(4-chlorophenyl)ethane (DDD) by Ralstonia eutropha strain A5

A Hay

Abstract: Evidence is presented demonstrating the ability of Ralstonia eutropha A5 to degrade 1,1‐dichloro‐2,2‐bis(4‐chlorophenyl)ethane (DDD) aerobically. Strain A5 was able to effect significant transformation of [14C]DDD: the hexane extractable radioactivity decreased to approximately 50% of the controls while more than 25% of the total radioactivity became associated with the acidified culture supernatant. There was also an increase in the amount of radioactivity associated with the cell pellet when compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
1
12
1
Order By: Relevance
“…The sequential fragments at m/z = 181 and 152 likely arise from the loss of both chlorines and the further loss of CHO from the base peaks, respectively. These characteristics were previously reported during description of the fragment ions in the mass spectra of monohydroxy-DDT isomers (Nadeau et al 1994) and monohydroxy-DDD isomers (Hay and Focht 2000).…”
Section: Identification Of Monohydroxy-ddt and -Dddsupporting
confidence: 67%
“…The sequential fragments at m/z = 181 and 152 likely arise from the loss of both chlorines and the further loss of CHO from the base peaks, respectively. These characteristics were previously reported during description of the fragment ions in the mass spectra of monohydroxy-DDT isomers (Nadeau et al 1994) and monohydroxy-DDD isomers (Hay and Focht 2000).…”
Section: Identification Of Monohydroxy-ddt and -Dddsupporting
confidence: 67%
“…Microorganisms from many different genera are capable of degrading DDT, promoting the loss of HCl via reductive dechlorination and producing DDD as a metabolite, and DDD can undergo reductive dehalogenation (Subba-Rao and Alexander 1985) or hydroxylation of aliphatic moieties (Bumpus and Aust 1987). Hay and Focht (2000) have demonstrated that DDD can be also transformed via dioxygenation and ring fission. Biodegradation using fungi has received relatively little attention compared to the process using bacteria, however, the proposed mechanism of degradation was similar to that in bacteria.…”
mentioning
confidence: 99%
“…2,3-dihydroxy-DDT would be further metabolized through meta-ring cleavage to form the yellow ring fission product, which would then be catabolized to 4-chlorobenzoic acid (4-CBA). The bacterium Ralstonia eutropha A5 grown on biphenyl was also shown to degrade DDD to form single-ring aromatic compounds via hydroxylation of the aromatic ring and subsequent meta-ring cleavage (Hay and Focht 2000). However, there is Values are means ± SD of triplicate samples limited information on the transformation of DDT and its metabolites via hydroxylation at the aromatic ring and ring cleavage reaction by white rot fungi at present.…”
Section: Discussionmentioning
confidence: 99%
“…This estimation would be supported by the result that mono-and dihydroxylated products were detected in both fungal cultures. Based on these results, we proposed that in Phlebia species, the mechanism for hydroxylation of aromatic ring differ from in bacteria (Nadeau et al 1994;Hay and Focht 2000), and the cytochrome P-450 monooxygenase system plays an important role in the Fig. 3 Proposed pathway for the degradation of DDT by P. lindtneri and P. brevispora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation